The effect of the bend on technique and performance during maximal speed sprinting - Churchill, S. M.; Salo, A. I. T.; Trewartha, G. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
For 200 and 400 m races half of the race is run around the bend. This study aimed to understand the changes in kinematics that occur during maximal effort bend sprinting. Velocity reduction (5%) on the bend compared to the straight was, for the left step, mainly due to increased (20%) touchdown distance and some angular kinematics changes which led to increased contact time and reduced step frequency. During the right step, performance dropped mainly due to a reduction in step length. It is likely that changes caused by inward lean, to counteract moments caused by centripetal forces, on the bend contributed to detrimental changes in sagittal plane kinematics (e.g. knee flexion at touchdown) normally associated with superior performance in sprinting. Similar to straight sprinting, reduced touchdown distance could hold the key to improve bend performance.